2006
DOI: 10.1038/sj.ejhg.5201614
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from autoimmune thyroiditis of skewed X-chromosome inactivation in female predisposition to autoimmunity

Abstract: The etiologic factors in the development of autoimmune thyroid diseases (AITDs) are not fully understood. We investigated the role of skewed X-chromosome inactivation (XCI) mosaicism in female predisposition to AITDs. One hundred and ten female AITDs patients (81 Hashimoto's thyroiditis (HT), 29 Graves' disease (GD)), and 160 female controls were analyzed for the androgen receptor locus by the HpaII/polymerase chain reaction assay to assess XCI patterns in DNA extracted from peripheral blood cells. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
71
6
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 29 publications
9
71
6
3
Order By: Relevance
“…[11][12][13] In accordance with these studies, we found a statistically significant positive association between XCI and the serum concentrations of TPOAb in euthyroid subjects (within-cohort analysis). To evaluate whether this association was causal or could be explained by the presence of genetic or environmental confounders, we also analysed the association between XCI and TPOAb within MZ and DZ pairs.…”
Section: Discussionsupporting
confidence: 77%
“…[11][12][13] In accordance with these studies, we found a statistically significant positive association between XCI and the serum concentrations of TPOAb in euthyroid subjects (within-cohort analysis). To evaluate whether this association was causal or could be explained by the presence of genetic or environmental confounders, we also analysed the association between XCI and TPOAb within MZ and DZ pairs.…”
Section: Discussionsupporting
confidence: 77%
“…These endocrine problems may be related to direct RNA toxicity in the hypothalamic-pituitary axis, or to a direct effect of RNA toxicity on the thyroid-perhaps through an autoimmune mechanism or the induction of apoptosis in the thyroid cells. A skewed AR has been previously reported in patients with thyroid problems related to autoimmune disease [Brix et al, 2005;Ozcelik et al, 2006], but in this study there was no difference in the AR between those with and without thyroid disease. Surprisingly, there was also no difference in the AR in females with and without FXTAS.…”
Section: Discussioncontrasting
confidence: 51%
“…The study revealed a similar age-related frequency of skewed XCI in both cases and controls, thus implying that PBC is not associated with an enhanced rate of skewed XCI in contrast with the data in autoimmune thyroid disease and scleroderma. [30][31][32] However, these latter findings were based on limited numbers of informative subjects and did not include age-matched controls; in fact, although variable prevalence rates of a skewed XCI status have been reported, studies taking into account age as a modifier factor, clearly indicate that as many as 16% of healthy women over the age of 50 are characterized by a severe XCI skewing. 11,12,25,33 Importantly, we also ruled out the possibility that preferential X loss and skewed XCI could be related to each other.…”
Section: Discussionmentioning
confidence: 93%
“…26 In addition, monosomy or major structural abnormalities of the X chromosome, as seen in Turner's syndrome 27,28 and premature ovarian failure, 29 are often characterized by autoimmune features. Following our recent findings of an enhanced monosomy X in peripheral lymphocytes of women with PBC or other autoimmune diseases 8,9 and reports of a frequent skewed XCI in women with non hepatic autoimmune diseases, [30][31][32] we have now investigated the mechanisms of X loss and XCI in 166 women with PBC, 49 with CHC and 177 healthy controls. We speculated that a specific hemizygous status of the monosomic X might unmask peculiar haplotypes responsible for susceptibility to autoimmunity.…”
Section: Discussionmentioning
confidence: 99%